Pawnshop Marketing Strategies to Increase Customer Interest - Hasanah, Ulfatul; Qibtiyah, Desy Bariyyatul (Al-Qalam Institue, 2025)
Marketing strategy plays a crucial role in promoting pawn products to the wider community. This study aims to analyze the marketing strategies employed in promoting pawn services by two financial institutions with different operational approaches. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The findings reveal that one institution adopts a digital-based strategy, utilizing social media and fast service to attract customers. At the same time, the other emphasizes a community-based approach grounded in religious values and local engagement. These distinct strategies are tailored to the social and cultural characteristics of the communities they serve. The study highlights that marketing strategies must be flexible and adaptive, rather than uniform, depending on contextual factors. The integration of digital outreach with community and value-based promotion is identified as a potentially effective and sustainable approach for expanding customer interest and loyalty in pawn services. In the context of education, these findings imply the importance of incorporating adaptive marketing and cultural sensitivity into business and economics curricula, particularly in courses related to financial services, entrepreneurship, and community engagement. Such integration can prepare students to develop responsive and contextually aware strategies in diverse market environments.